If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1x = 4x + 19 Reorder the terms: 4 + -1x = 19 + 4x Solving 4 + -1x = 19 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + -1x + -4x = 19 + 4x + -4x Combine like terms: -1x + -4x = -5x 4 + -5x = 19 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + -5x = 19 + 0 4 + -5x = 19 Add '-4' to each side of the equation. 4 + -4 + -5x = 19 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 19 + -4 -5x = 19 + -4 Combine like terms: 19 + -4 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= | | 15z+30=15y+30 | | 6(W+3)=-2(5W-5)+2W | | 3(9+1)-5=(2y-2) | | k-7=10k-16 | | x^3-4x^2+x-9=0 | | 3i+10=14i-12 | | n^2-81= | | 8y+20=16-12 | | 7/2x=-21 | | 6x-5=8x+13 | | e^2x=1/9 | | -54+12x=6(x-3) | | F=1/9k(d-n) | | 6-3/4x=9 | | 6a^2-10=422 | | 3/7=r/4 | | 8(r+3)=72 | | 47=-2-7x | | -1x-52=x^2+6x+6 | | -0.0018x^2+0.06x+1.5=0 | | 3/4x-9=8 | | -3/2x-6 |